Design and test of hydro-pneumatic ISD suspension in heavy multi-axle vehicles - Jiamei Nie (SAGE Publishing, 2021)
Aiming to improve the road friendliness so as to reduce the road damage caused by heavy multi-axle vehicles, and to enhance the ride comfort, we propose a kind of hydro-pneumatic ISD suspension structure, which is equivalent to a two-stage ISD structure integrating a traditional hydro-pneumatic suspension and a fluid inerter. Firstly, based on the 1/4 model, a genetic algorithm is used to optimize the key structural parameters of hydro-pneumatic ISD suspension. Secondly, the AMESim dynamic model of heavy multi-axle vehicles is built for the performance comparison between the traditional hydraulic and hydro-pneumatic ISD suspensions. Finally, this paper machines a hydro-pneumatic ISD suspension to replace the traditional hydraulic one in a heavy multi-axle vehicle to carry out a road test. Test results indicate that the proposed suspension can effectively restrain the vibrations of sprung and unsprung mass and improve ride comfort as well as road friendliness. The hydro-pneumatic ISD suspension can be applied to engineering.